Makna kearifan budaya Jawa dalam puisi Pariksit, Telinga, Dongeng Sebelum Tidur, dan Asmaradana - Suwignyo, Heri (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2013)
The interpretation of Javanese wisdom can be found in Indonesian modern poetry by decoding the cultural traditions of wayang stories, mystical narratives, and folklore. One form of Javanese wisdom, ojo dumeh (do not be arrogant), is found in the poem Parksit and revealed in Chapter VII. The poem Telinga exposes the Javanese cultural value of manunggaling kawula Gusti (self-discovery), derived from the mystical story of Dewa Ruci. The poems Asmaradana and Dongeng Sebelum Tidur show the meanings of sincerity, sacrifice, and firmness in keeping promises, which are inspired by the folktales King Anglingdarma and Damarwulan.